Multikinase Inhibitor Treatment Patterns for Advanced Thyroid Cancer in Japan: An Administrative Claims Database Study - Chie Masaki; Kiminori Sugino; Yoshinori Tanizawa; Kenichi Nakamura; Yui Okada; Zhihong Cai; Takahiro Okamoto (Adis, Springer Healthcare, 2022)
Abstract Background The multikinase inhibitors (MKIs) sorafenib, lenvatinib, and vandetanib are approved for advanced thyroid cancer (TC) in Japan. How sequential treatment with MKIs is conducted in Japanese clinical practice is unknown. Methods This retrospective observational cohort study used a Japanese administrative claims database (April 2008-September 2021). Patients with a confirmed TC subtype diagnosis of papillary (PTC), follicular (FTC), medullary (MTC), or anaplastic (ATC), who received MKI treatment after TC diagnosis within the index period (June 2014-August 2021), were included. Overall MKI treatment duration was estimated by Kaplan-Meier analysis. Results The analysis population included 795 patients (PTC, N = 447; FTC, N = 86; MTC, N = 32; ATC, N = 230). Median age was ≥ 64 years; most patients (> 60%) were female except for the MTC subgroup (43.8%). First-line (1L) MKI treatment was mainly lenvatinib for PTC (81.7%), FTC (83.7%), and ATC (97.8%), and vandetanib for MTC (62.5%). Among patients discontinuing 1L MKI treatment and evaluable for subsequent therapy [PTC: 57.9% (259/447); FTC: 48.8% (42/86); MTC: 62.5% (20/32); ATC: 70.4% (162/230)], 26.3% (68/259), 21.4% (9/42), 50.0% (10/20), and 4.9% (8/162) of PTC, FTC, MTC, and ATC patients, respectively, received second-line (2L) treatment. Median (95% CI) overall MKI treatment duration was 21.2 (17.9-27.5), 43.9 (30.9-not assessable), 39.0 (17.7-not assessable), and 4.0 (3.0-4.8) months for PTC, FTC, MTC, and ATC, respectively. Conclusion Advanced TC treatment options are limited. In this study, most patients received only 1L MKI treatment; of those who discontinued 1L, ≤ 50% progressed to 2L.